PENGARUH KUALITAS PRODUK DAN GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERAWATAN KULIT AVOSKIN MELALUI RATING SELLER SEBAGAI VARIABEL INTERVENING (STUDI KASUS GENERASI Z PEMAKAI PRODUK AVOSKIN) - Salsabila, Valina Adzra; Setiarini; Noor, Laili Savitri (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
The field of beauty products continues to experience very rapid development so that a company is required to be more creative in marketing its products. The purpose of this study is to analyze how the influence of product quality and green marketing on the purchase decision of Avoskin skin care products with seller rating as an intervening variable both directly and indirectly. The sample used in this study was 167 respondents with criteria, namely: covering generation Z (1997-2012) and users of Avoskin products and using Non Probability Sampling with Purposive Sampling techniques. The results of this study show that there is a positive and significant influence on product quality on rating seller, there is a positive and significant influence of green marketing on rating seller, there is a positive and significant influence on product quality on purchasing decisions, there is a positive and significant influence of green marketing on purchasing decisions, There is a positive and significant influence of seller assessment on purchasing decisions, There is a positive and significant influence of Product Quality on Purchasing Decisions With rating seller as an intervening variable, there is a positive and significant influence of green marketing on purchasing decisions with rating seller as an intervening variable.